Learning and understanding human skill - Urbančič, Tanja (Informatica (Ljubljana), 2001)
Research results in machine learning have confirmed the possiblitily of reconstruction of human skill, resulting in similar or even improved performance of the same skill by a computer program. The methods that build symbolic models of skills are preferred if generated models are to be used help humans in improving their own skill. The paper discusses these possibilities with the objective of accelerating and enhancing the process of human skill development. Experiments in learning control of dynamic systems are presented and wider potential of applications in assisting learning of skill is discussed.
Keywords: razum; reason; razumevanje; modeliranje; strojno učenje